2019
DOI: 10.3390/molecules24213951
|View full text |Cite
|
Sign up to set email alerts
|

The Early Years of 2,2′-Bipyridine—A Ligand in Its Own Lifetime

Abstract: The first fifty years of the chemistry of 2,2′-bipyridine are reviewed from its first discovery in 1888 to the outbreak of the second global conflict in 1939. The coordination chemistry and analytical applications are described and placed in the context of the increasingly sophisticated methods of characterization which became available to the chemist in this time period. Many of the “simple” complexes of 2,2′-bipyridine reported in the early literature have been subsequently shown to have more complex structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 274 publications
(323 reference statements)
2
79
0
1
Order By: Relevance
“…In its dominant oxidation state II, the d 9 electronic configuration confers elongated or shortened axial axes, known as the Jahn–Teller effect, [3] and depending on the coordinating ligands various geometries and stereoisomers, that is, cis – trans for CuX 2 (N‐N) 2 where N‐N’ is a bidentate ligand, can be obtained. 2,2’‐Bipyridine (bpy) has been extensively used in coordination chemistry as a bidentate ligand [4] and in catalysis [5] . The catalytic protocols that involve in situ blending of bpy, copper salts and substrates achieve high yields and new products; [6] however, the role of each component in the catalytic cycle is questioned.…”
Section: Introductionmentioning
confidence: 99%
“…In its dominant oxidation state II, the d 9 electronic configuration confers elongated or shortened axial axes, known as the Jahn–Teller effect, [3] and depending on the coordinating ligands various geometries and stereoisomers, that is, cis – trans for CuX 2 (N‐N) 2 where N‐N’ is a bidentate ligand, can be obtained. 2,2’‐Bipyridine (bpy) has been extensively used in coordination chemistry as a bidentate ligand [4] and in catalysis [5] . The catalytic protocols that involve in situ blending of bpy, copper salts and substrates achieve high yields and new products; [6] however, the role of each component in the catalytic cycle is questioned.…”
Section: Introductionmentioning
confidence: 99%
“…Part of our motivation for this present work lies in a survey we recently published of early 2,2'bipyridine (bpy) complexes in which we showed that many of the "simple" transition metal compounds [MX n L p ] (X = anion, L = oligopyridine) were actually coordination polymers. [3] The survey of the compounds in this review leads to a general description of 1D, 2D or 3D systems decorated with oligopyridines. Only in a very few cases do the oligopyridines interact with more than one metal centre and play a role in the propagation of the polymer or the network.…”
Section: Topology and Dimensionalitymentioning
confidence: 99%
“…This compound has been used as a precursor for the preparation of PbO nanoparticles. [92] The thermal decomposition of the 1D polymeric complex {Pb 3 (3,4,7, phen) (µ-N 3 ) 5 (µ-NO 3 )} n also leads to PbO nanoparticles. [93] The polynuclear motif is also extended into decorated 2D sheets.…”
Section: Group 14 Elementsmentioning
confidence: 99%
“…There is a large body of crystallographic data for metal complexes of these ligands in the Cambridge Structural Database (using version 5.41) and we have, in general, restricted our coverage to complexes containing the parent compound 2,2'-bipyridine in order to eliminate the influence of other interactions between the halogen and substituents on the ligand. Furthermore, the chemistry of these ligands and their complexes is exceptionally well documented [23][24][25][26][27][28][29][30][31][32][33][34][35][36], facilitating correlations between the solid-state features and chemical behaviour.…”
Section: The Oligopyridinesmentioning
confidence: 99%